Thyrotropinoma with silent somatotroph and lactotroph adenoma during pregnancy. (22nd September 2022) - Wu, Yu-Fang; Ng, Hui Yi; Namboodiri, Divya; Lewis, David; Davidson, Andrew; Champion, Bernard; Preda, Veronica
Abstract : Summary: Thyrotropinomas are an uncommon cause of hyperthyroidism and are exceedingly rarely identified during pregnancy, with limited evidence to guide management. Most commonly they present as macroadenomas and may cause symptoms of mass effect including headache, visual field defects and hypopituitarism. We present a case of a 35-year-old woman investigated for headaches in whom a 13 mm thyrotropinoma was found. In the lead-up to planned trans-sphenoidal surgery (TSS), she spontaneously conceived and surgery was deferred, as was pharmacotherapy, at her request. The patient was closely monitored through her pregnancy by a multi-disciplinary team and delivered without complication. Pituitary surgery was performed 6 months post-partum. Isolated secondary hypothyroidism was diagnosed postoperatively and replacement thyroxine was commenced. Histopathology showed a double lesion with predominant pituitary transcription factor-1 positive, steroidogenic factor negative plurihormonal adenoma and co-existent mixed thyroid-stimulating hormone, growth hormone, lactotroph and follicle-stimulating hormone staining with a Ki-67 of 1%. This case demonstrates a conservative approach to thyrotropinoma in pregnancy with a successful outcome. This highlights the need to consider the timing of intervention with careful consideration of risks to mother and fetus. Learning points: Thyrotropinomas are a rare cause of secondary hyperthyroidism. Patients may present with hyperthyroidism or symptoms of mass effect, including headaches or visual disturbance. Thyrotropinoma in pregnancy presents a number of pituitary-related risks including pituitary apoplexy and compression of local structures. Hyperthyroidism in pregnancy raises the risk of complications including spontaneous abortion, preeclampsia, low birthweight and premature labour. Timing of medical and surgical therapies must be carefully considered. A conservative approach requires careful monitoring in case emergent intervention is required.